A STUDY OF THE RELATIONSHIP BETWEEN APARTMENT OCCUPANCY PATTERNS AND STUDENT BEHAVIOR PATTERNS Case Study: Gading Icon Apartment - Ari Widyati Purwantiasning; Mohammad Baskoro; Muhammad Ibnu Fachry; Rustama Fasda Bimaktumaru (Department of Architecture Universitas Muhammadiyah Jakarta, 2023)
Apartment is a room or several rooms (rooms) that are functioned or designated as a place to live, located in a building that usually has other rooms or rooms and the like. This study attempts to explore and analyze the relationship between residential space patterns and student behavior patterns in Jakarta. The behavioral patterns of students that affect the pattern of vertical residential spaces not only have an impact on the behavior and form of space but also see how student behavior shapes architecture in residential space patterns and architecture shapes student behavior. The purpose of this study is to understand the theory related to the relationship between vertical residential space patterns and student behavior patterns, to understand the characteristics of the relationship between residential space patterns and student behavior, to understand environmental factors for student behavior. The research method taken on the research approach uses a qualitative descriptive method. The data studied and obtained are physical and non-physical data obtained from interviews, observations, and mapping of student behavior patterns in residential spaces of Jakarta apartments. The approach that will be used is the Human Behavior approach to students in apartment housing. From the analysis of behavior patterns carried out, student activities are quite dense, causing the use of furniture according to needs and has ergonomic characteristics.